Relationship between corticosteroid use and incidence of ventilator-associated pneumonia in COVID-19 patients - Saura, Ouriel (2022)
Funding This study was supported in part by a grant from the French government through the « Programme Investissement d’Avenir» (I-SITE ULNE) managed by the Agence Nationale de la Recherche (coVAPid project). Prof. Ignacio Martin-Loeches has been supported by SFI (Science Foundation Ireland), Grant number 20/COV/0038. The funders of the study had no role in the study design, data collection, analysis or interpretation, writing of the report or deci sion to submit for publication.